Comparing voting by committees according to their manipulability - Arribillaga, Roberto Pablo (2017)
We consider the class of voting by committees to be used by a society to collectively choose a subset from a given set of objects. We offer a simple criterion to compare two voting by committees without dummy agents according to their manipulability. This criterion is based on the set- inclusion relationships between the two corresponding pairs of sets of objects, those at which each agent is decisive and those at which each agent is vetoer. We show that the binary relation "to be as manipulable as" endows the set of equivalence classes of anonymous voting by committees (i.e., voting by quotas) with a complete upper semilattice structure, whose supremum is the equivalence class containing all voting by quotas with the property that the quota of each object is strictly larger than one and strictly lower than the number of agents. Finally, we extend the comparability criterion to the full class of all voting by committees.